Analyzing the Role of Silicon in Leaf C:N:P Stoichiometry and Its Effects on Nutritional Efficiency and Dry Weight Production in Two Sugarcane Cultivars - de Souza Júnior, Jonas Pereira [UNESP]; de Oliveira, Tainara Lopes [UNESP]; de Mello Prado, Renato [UNESP]; de Oliveira, Kevein Ruas [UNESP]; Soares, Mariana Bomfim [UNESP] (Springer Nature, 2022)
This study aimed to assess the effects of Si fertigation on the leaf C:N, C:P, and C:Si ratios, nutritional efficiency, and plant development of two sugarcane cultivars. The experiments consisted of two treatments: absence and presence (2.5 mM) of Si supplied by fertigation, in a completely randomized design with ten repetitions. The experiments were completed 125 days after transplanting, when plant height, stalk diameter, number of tillers, and leaf and stalk dry weight were measured. In the leaves, Si, N, P, and C concentration and accumulation were determined, as well as N, P, and C use efficiency and the C:N, C:P, and C:Si ratios. When applied to sugarcane via fertigation, Si increased the absorption of Si, N, and P and plant development. Si fertigation is efficient in sugarcane because it modifies leaf C:N, C:P, and C:Si ratios, improving N, P, and C use efficiency and crop growth. The beneficial effect of Si on sugarcane development was evidenced by the increase in plant height, stalk diameter, number of tillers, leaf area, and leaf and stalk dry weight. Our results demonstrate that Si fertigation is efficient in the two sugarcane cultivars studied because it modified the C:N; C:P; and C:Si stoichiometric ratios, improving N, P, and C use efficiency.
Keywords: Pre-sprouted seedlings; Saccharum officinarum; Silicon fertigation; Stoichiometry; Sugarcane development